On the Mechanical Modeling of Tensegrity Columns Subject to Impact Loading - Amendola, Ada; Favata, Antonino; Micheletti, Andrea (Frontiers in Materials, 2018)
A physical model of a tensegrity columns is additively manufactured in a titanium alloy. After removing sacrificial supports, such a model is post-tensioned through suitable insertion of Spectra cables. The wave dynamics of the examined system is first experimentally investigated by recording the motion through high-speed cameras assisted by a digital image correlation algorithm, which returns time-histories of the axial displacements of the bases of each prism of the column. Next, the experimental response is mechanically simulated by means of two different models: a stick-and-spring model accounting for the presence of bending-stiff connections between the 3D-printed elements (mixed bending-stretching response), and a tensegrity model accounting for a purely stretching response. The comparison of theory and experiment reveals that the presence of bending-stiff connections weakens the nonlinearity of the wave dynamics of the system. A stretching-dominated response instead supports highly compact solitary waves in the presence of small prestress and negligible bending stiffness of connections.